IMPLEMENTATION OF FILING SYSTEM IN ACTIVE ARCHIVE STORAGE AT FACULTIES IN INSTITUT PERTANIAN BOGOR: Array - 1 (Jurnal Kearsipan, 2021)
This research aims to determine the implementation of active archive filing system at the Faculties in IPB University. This research was a descriptive research using qualitative approach. The informants of this research were archive managers at the faculties in IPB University. Data collection techniques used observation, questionnaires, interviews, and literature study. The results showed that: 1) 75% of archive managers at the Faculties in IPB University had already understand the filing, 2) 53.2% of archive managers at the Faculties in IPB University had not carried out filing in accordance with the applicable archiving principles, due to the limited facilities and infrastructure, 3) 54.2% of archive managers at the Faculties in IPB University had realized that active archives must be stored properly, because it will make it easier for depreciation. To make each work unit to carry out filing properly, it is necessary to provide technical guidance for archive managers as well as adequate facilities and infrastructure.